Highlighting of Urinary Sodium and Potassium among Indonesian Schoolchildren Aged 9–12 Years: The Contribution of School Food - Farapti Farapti; Muji Sulistyowati; Kurnia Dwi Artanti; Stefania Widya Setyaningtyas; Sri Sumarmi; Bibit Mulyana (Journal of Nutrition and Metabolism)
Background. Sodium (Na) and potassium (K), the essential nutrients, have vital role in promoting cellular growth including growth and development of children. Excessive Na intake and inadequate K consumption, which consequently increases the risk of cardiovascular disease, have been reported. Spot electrolyte urine was highly correlated and validated with gold standard to estimate electrolyte dietary intake. This study aimed at predicting sodium and potassium intake using morning spot urine among Indonesian schoolchildren. Methods. A cross-sectional study was carried out in 155 healthy elementary students aged 9–12 years. Spot urine samples were collected and analyzed for Na, K, and creatinine. Predicted 24 h Na and K excretions were compared to the Indonesian recommendation dietary allowances. The Na and K contribution from school food was reported by observing directly and the dietary recall method. Results. A total of 80 boys and 75 girls recruited as samples in this study demonstrated that their estimated urinary Na and K were 105.42 ± 66.05 mmol/day and 16.39 ± 12.57 mmol/day, respectively. Na intake was on average higher than recommended; meanwhile, almost all subjects showed very low compliance of K intake recommendation. Furthermore, food intake at school contributed to those conditions. Na and K content of school food contributed 33% and 29% of the daily intake of each nutrient and contributed 125% and 25% higher than the Na and K school standard, respectively. Conclusions. Indonesian schoolchildren aged 9–12 years are categorized by excessive Na intake and very deficient K intake. The present study highlights the need for policies in the environmental school setting to reduce Na intake and K intake.